2021
DOI: 10.48550/arxiv.2107.06660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infrared and Holographic Aspects of the $S$-Matrix in Gauge Theory and Gravity

Abstract: Soft theorems in gauge theory and gravity encode the universal properties of scattering amplitudes as the zero frequency limit of one or more external states is approached. When the participating particles are treated in the massless limit, the soft theorems are known to depend only on the directions of the states on null infinity. Leveraging this fact, we develop dual two-dimensional descriptions of soft theorems, recasting them as Ward identities of such dual models on the celestial sphere. This is done by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 181 publications
(274 reference statements)
0
7
0
Order By: Relevance
“…We believe that our result lends support to the holographic interpretation of the celestial CFT formalism. There is a small body of previous work addressing soft exchange in celestial CFT, primarily in four dimensions [2][3][4][5][6][7][8]. The methods and rationale in these treatments differ significantly from ours but the results for the case d " 2 are equivalent.…”
Section: Introductionmentioning
confidence: 73%
“…We believe that our result lends support to the holographic interpretation of the celestial CFT formalism. There is a small body of previous work addressing soft exchange in celestial CFT, primarily in four dimensions [2][3][4][5][6][7][8]. The methods and rationale in these treatments differ significantly from ours but the results for the case d " 2 are equivalent.…”
Section: Introductionmentioning
confidence: 73%
“…The former would be related to the (partial) sub-subleading soft gluon factorization [32]. In this context, it would be important to make contact with the "celestial" 2d CFT approach to symmetries [58][59][60][61][62][63][64][65], which naturally incorporates higher order factorization formulas satisfying a rich algebraic structure [34,66].…”
Section: Discussionmentioning
confidence: 99%
“…While this problem remains more or less intractable for the full dynamics of four-dimensional gravity, it turns out to be considerably simpler to ask intelligent questions as long as we restrict our attention to the soft sector of gravity. Indeed, in a recent series of papers due to the present author [29,36,37], it was shown that in the case of QED and gravity, the leading order soft sectors are dynamically captured by theories that are entirely two dimensional. In the case of QED, this theory turns out to be the simple case of a free boson on the sphere, while in the case of gravity this theory is that of a two-dimensional field obeying a biharmonic equation.…”
Section: Introductionmentioning
confidence: 92%
“…Specifically, we will study this problem in the context of the two-dimensional duals that we now know describe the soft part of gravity at leading order. Indeed, since we now know that the soft theorems are really invariance under supertranslations in disguise, we will recast the entire problem of constructing supertranslation eigenstates in terms of the two-dimensional models of [29,36,37]. In concrete terms, we will give a prescription of how to construct eigenstates of supertranslations given a list of supermomenta in terms of the dual two-dimensional model of soft gravity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation